(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
“When you decide to lead a clean life, chastity will not be a burden on you it will be a crown of triumph.” -St. Josemaria EscrivaNo one has the right to interfere in other people’s personal lives, but when it becomes necessary to save and preserve society’s culture, traditions, and dignity, it is necessary to do so, i.e. to investigate a type of intimate relationship that is gaining a lot of attention in contemporary India, namely the pre-marital relationship. It’s time to investigate the family’s role in pre-marital relationships of young adults in order to challenge the language of individual agency and freedom that is frequently linked with pre-marital relationships. The researcher claims in this article that, while pre-marital relationships may appear to be a break from the marriage narrative, they are really modelled after the forms and expectations of a married partnership. The methods in which families position themselves in respect to pre-marital relationships are also examined in this study. Specifically, it discusses the strategies by which the family can obstruct or encourage certain pre-marital relationships over others, thereby highlighting the bearing of the family’s involvement in changing the course of a relationship either from a non-serious form of relationship to a committed one, or leading to the breaking up of the relationship.